Study of Os Zygomaticum Bipartitum In Skulls of Central India - Mangalgiri, Ashutosh S; Satpathy, Dibya K; Bhojwani , Rajendra (Journal of Indian Academy of Forensic Medicine, 2015)
Zygomatic bone is commonly known as cheek bone, forms prominence of cheek. Present study was conducted on 228 zygomatic bones of 114 dry skulls. Zygomatic bone may divide into two parts either by horizontal or vertical suture. A horizontal suture was observed dividing the zygomatic bone into two parts in two zygomatic bones out of 228 zygomatic bones studied (0.87%). An inferior type of horizontal suture was observed dividing the zygomatic bone. Two zygomatic bones belong to the same skull i.e. bilateral bipartite zygomatic bone. Suture can be well identified by radiography and CT scan. Primary cartilaginous joint between sphenoid and basi-occiput was not ossified. Complete metopic suture was also observed. Condition is a rare one and therefore can be easily misinterpreted as zygomatic bone fracture in medico legal cases. Therefore the condition should be kept in mind by Forensic experts and maxillofacial surgeons. Both CT scan and Radiography are important tolls in the diagnosis of zygomatic suture and should be considered as primary diagnostic tools in the diagnosis of suture. Presence of zygomaticum bipartitum is addition to the literature.